An optimal energy-efficient resource allocation algorithm in ultra-dense network - Yueyue ZHANG; Weiwei XIA; Yaping ZHU; Feng YAN; Xuzhou ZUO; Lianfeng SHEN (Dianxin kexue)
The energy-efficient resource allocation problem was taken in an ultra-dense network(UDN) consisted of multiple femtocells.Aiming at maximizing the energy efficiency (EE) of the whole network,quality of service (QoS) constraint and interference limitation was considered.Then,the established nonconvex and nonlinear problem was relaxed relying on Cauchy inequality,and was developed into a non-cooperative game.Additionally,a distributed EE maximization algorithm was proposed satisfying the max-min fairness (MMF) criterion.Simulation results show that the proposed algorithm outperformances the existing algorithms in terms of the EE and the throughput.